Sex differences in adipose insulin resistance are linked to obesity, lipolysis and insulin receptor substrate 1 - Arner, Peter; Viguerie, Nathalie; Massier, Lucas; Rydén, Mikael; Astrup, Arne; Blaak, Ellen; Langin, Dominique; Andersson, Daniel Peter (INTERNATIONAL JOURNAL OF OBESITY, 2024)
Background/Objective Insulin resistance is more prominent in men than women. If this involves adipose tissue is unknown and was presently examined. Subjects/Methods AdipoIR (in vivo adipose insulin resistance index) was measured in 2344 women and 787 men. In 259 of the women and 54 of the men, insulin induced inhibition of lipolysis (acylglycerol breakdown) and stimulation of lipogenesis (glucose conversion to acylglycerols) were determined in subcutaneous adipocytes; in addition, basal (spontaneous) lipolysis was also determined in the fat cells. In 234 women and 115 men, RNAseq expression of canonical insulin signal genes were measured in subcutaneous adipose tissue. Messenger RNA transcripts of the most discriminant genes were quantified in 175 women and 109 men. Results Men had higher AdipoIR values than women but only when obesity (body mass index 30 kg/m 2 or more) was present ( p < 0.0001). The latter sex dimorphism was found among physically active and sedentary people, in those with and without cardiometabolic disease and in people using nicotine or not ( p = 0.0003 or less). In obesity, adipocyte insulin sensitivity (half maximum effective hormone concentration) and maximal antilipolytic effect were tenfold and 10% lower, respectively, in men than women ( p = 0.005 or less). Basal rate of lipolysis was two times higher in men than women ( p > 0.0001). Sensitivity and maximum effect of insulin on lipogenesis were similar in both sexes ( p = 0.26 and p = 0.18, respectively). When corrected for multiple comparison only RNAseq expression of insulin receptor substrate 1 ( IRS1 ) was lower in men than women ( p < 0.0001). The mRNA transcript for IRS1 was 60% higher in women than men ( p < 0.0001). Conclusions In obesity, adipose tissue insulin resistance is more pronounced in men than in women. The mechanism involves less efficient insulin-mediated inhibition of adipocyte lipolysis, increased basal rate of lipolysis and decreased adipose expression of a key element of insulin signaling, IRS1 .